PERANAN GOOD CORPORATE GOVERNANCE DALAM PENCEGAHAN FRAUD (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2014)
Corruption, misappropriation of assets and fraudulent statements are types of fraudthat adversely affect the performance of the company/organization. Various types offraud are common in the private sector or other government organizations.Empirically research showed that fraud occurred due to weak implementation ofCorporate Governance. It is important for all stakeholders, especially themanagement company to comprehensively understand the consep of fraud, includesknowing why a person committing or engaging in fraudulent activity and all of the redflags. Implementation of internal and external mechanism of Corporate Governacemechanism by considering all of its principles and functions also audit committeefunction, predicted to be able to reduce the occurrence of fraud.Keywords: Fraud, corporate governance principles, corporate governance functionsand audit committee.